Congregational Analysis: a theological and ministerial approach - Malan Nel (HTS Teologiese Studies/Theological Studies, 2009)
The research problem concerned is: what criteria should be used when congregations are analysed? Congregations as faith communities are defined differently. Identifying the local congregation as a defined and as an empirical subject plays a major role in answering the research question. The theological departure points taken are that any measure of a local congregation has to deal with issues like faithfulness to the gospel and the missional identity and integrity of the congregation as a contextual faith community. The hypothesis is that when theologically informed and motivated congregations can and should be analysed in the process of continuing reformation. While the first article described the approach and outcome of empirical research, this article focuses mainly on understanding the church as intermediary in its ministerial role-fulfilment. Ministries are modes by which God is coming to his own and through them to his world. Eventually a case is made for congregational analysis as a test of faithfulness to this understanding of ministry.